H1N1 vaccination in Sjögren's syndrome triggers polyclonal B cell activation and promotes autoantibody production. Issue 10 (31st July 2017) - Brauner, Susanna; Folkersen, Lasse; Kvarnström, Marika; Meisgen, Sabrina; Petersen, Sven; Franzén-Malmros, Michaela; Mofors, Johannes; Brokstad, Karl A; Klareskog, Lars; Jonsson, Roland; Westerberg, Lisa S; Trollmo, Christina; et al.
Abstract : Objectives: Vaccination of patients with rheumatic disease has been reported to result in lower antibody titres than in healthy individuals. However, studies primarily include patients on immunosuppressive therapy. Here, we investigated the immune response of treatment-naïve patients diagnosed with primary Sjögren's syndrome (pSS) to an H1N1 influenza vaccine. Methods: Patients with Sjögren's syndrome without immunomodulatory treatment and age-matched and gender-matched healthy controls were immunised with an H1N1 influenza vaccine and monitored for serological and cellular immune responses. Clinical symptoms were monitored with a standardised form. IgG class switch and plasma cell differentiation were induced in vitro in purified naïve B cells of untreated and hydroxychloroquine-treated patients and healthy controls. Gene expression was assessed by NanoString technology. Results: Surprisingly, treatment-naïve patients with Sjögren's syndrome developed higher H1N1 IgG titres of greater avidity than healthy controls on vaccination. Notably, off-target B cells were also triggered resulting in increased anti-EBV and autoantibody titres. Endosomal toll-like receptor activation of naïve B cells in vitro revealed a greater propensity of patient-derived cells to differentiate into plasmablasts and higher production of class switched IgG. The amplified plasma cell differentiation and class switch could be induced in cells from healthy donors by preincubation with type 1 interferon, but was abolished in hydroxychloroquine-treated patients and after in vitro exposure of naïve B cells to chloroquine. Conclusions: This comprehensive analysis of the immune response in autoimmune patients to exogenous stimulation identifies a mechanistic basis for the B cell hyperactivity in Sjögren's syndrome, and suggests that caution is warranted when considering vaccination in non-treated autoimmune patients.